The Effect of Rotation on the Career Development of Civil Servant of the Educational Staff: A Case Study in Serang City, Indonesia - Murni Murni; Sholeh Hidayat; Nurul Anriani (Gagasan Pendidikan Indonesia, 2022)
This study aimed to determine the effect of career rotation on the career development of civil servant of the educational staff  in Serang city, Banten province, Indonesia. We used a quantitative approach and survey method with correlational techniques through multiple linear regression analysis. The method used in this study is case study. The data taken in this study is regarding career development and rotation of civil servant of the educational staff. The entire data is primary data, namely data from research respondents. The data was collected using a questionnaire in the form of an instrument. In this study, the results of regression linearity where the Fcount value was 0.825 and the probability significance value was 0.747 so that rotation positively affects the career development of civil servant of the educational staff in Serang City, Banten Province, Indonesia. It means that if the rotation is carried out on target, it will be followed by the career development of civil servant of the educational staff  in Serang city, Banten province, Indonesia.